Effects of prolonged exercise in the heat (31°c) and cool (18°c) environments on lactoferrin among recreational athletes - Bakar, Nor Azara Abu (Pusat Pengajian Sains Kesihatan, 2014)
The present study is a randomised, cross-over study that aims to determine the effects of prolonged exercise in the heat (31°C) and cool (18°C) environments on physiological changes and lactoferrin responses among recreational athletes. Thirteen healthy male recreational athletes (age: 20.9 ± 1.3 years old; body weight: 63.2 ± 7.8 kg) were recruited in this study. Each participant performed 2 separate running trials for 90 min at 60% V02max in a random order: running in the heat environment first, followed by running in the cool environment or vice versa. The recovery period between these two trials was one week. To prevent adverse effect of dehydration during exercise, cool plain water (3 mL.kg'1 body weights) was given to participants at every 20 min during trial. Participant’s nude body weight was measured pre and post exercise during each trial. Heart temperature, and relative humidity were recorded before warm-up, after warm-up, at every 20 min during trial, and at the end of trial. Blood samples were collected before warm-up, after warm up, at min 30 and 60 during trial, at the end of trial, and 1 h post exercise. Blood samples were used for haematological analysis (hemoglobin concentration). Saliva samples were collected pre and post and 1 h post exercise. From the saliva samples, x rate, rate of perceived exertion, oxygen uptake, skin and tympanic temperatures, room lactoferrin concentration was measured by ELISA and lactoferrin secretion rate was calculated. The data collected were analysed using two-way ANOVA with repeated measures to measure significant differences between groups and within groups. Results showed that body weight changes, heart rate, skin and tympanic temperatures were significantly higher in heat compared to cool trials (p 0.001). In addition, prolonged exercise significantly increased (p 0.05) lactoferrin concentration and secretion rate, haemoglobin concentration and plasma volume changes. Based on the results obtained, it can be concluded that in the present study, the physiological parameters had greater changes in the heat trial compared to cool trial whereas, lactoferrin responses (mucosal immunity) were not affected by ambient/room temperatures.